Antibiotic Resistance Profiles and Population Structure of Disease-associated Staphylococcus Aureus infecting Patients in Fort Portal Regional Referral Hospital, Western Uganda - Ackers-Johnson, Gavin; Kibombo, Daniel; Kusiima, Brenda; Nsubuga, Moses L.; Kajumbula, Henry M.; Goodhead, Ian B.; Birtles, Richard J.; James, Chloë E. (Microbiology, 2021)
Tackling antimicrobial resistance (AMR) is particularly challenging in low-resource settings such as Fort Portal Regional Referral Hospital (FPRRH) in Western Uganda. Specific knowledge of local AMR epidemiology is required to inform evidence-based improvement of antibiotic stewardship measures in the hospital. To address this, we combined existing antimicrobial susceptibility testing (AST) from FPRRH, with whole genome sequencing (WGS) of 41 Staphylococcus aureus isolates (2017–2019). AST revealed 73 % (30 of 41) of isolates were resistant to one or more antibiotics and 29 % (12 of 41) were multi-drug resistant (MDR). Resistance phenotypes were largely explained by the presence of antibiotic resistance genes in WGS data. Five isolates were methicillin-resistant S. aureus (MRSA) and MDR. Although all isolates were susceptible to clindamycin, a 24 % carriage of erm genes suggests potential for rapid development of resistance. We inferred a population structure for the S. aureus isolates by comparing their core genomes. Twenty isolates formed a tight cluster corresponding to multilocus sequence typing clonal complex (CC) 152, a CC found to be particularly prevalent in northern Africa. The frequency of genes associated with methicillin, chloramphenicol and ciprofloxacin resistance were significantly lower among CC152 strains than non-CC152 strains; thus, in keeping with previous work, we find that CC152 is almost exclusively methicillin-sensitive S. aureus (MSSA). Also, in agreement with other studies, we observed that the occurrence of Panton–Valentine leukocidin toxin-encoding genes was significantly higher among CC152 strains than non-CC152 strains. However, we also observed that the coagulase gene was over-represented in this CC, further defining the virulence strategy of this important pathogen. By generating detailed information about the epidemiology of circulating S. aureus and their antibiotic susceptibility, our study has provided, for the first time, data on which evidence-based infection and AMR interventions at FPRRH can be based.
Keywords: antibiogram; antibiotic resistance; comparative genomics; population structure; Staphylococcus aureus